Adjustable electrochemical properties of solid-solution MXenes. (October 2021) - Wang, Likui; Han, Meikang; Shuck, Christopher E.; Wang, Xuehang; Gogotsi, Yury
Abstract: MXenes are promising pseudocapacitive materials with ultrahigh specific capacitance. Currently, more than 30 stoichiometric MXene compositions and about 20 solid solutions have been experimentally synthesized. However, most studies focus on Ti3 C2 T x or a few other single-M MXenes, and little is known about the electrochemical properties of solid-solution MXenes. Herein, two sets of niobium-based solid-solution MXenes (Ti2−y Nby T x and V2−y Nby T x ; 0 ≤ y ≤ 2) were synthesized and the dependence of their electrochemical properties on the ratio of M elements in the structure was investigated. Relationships between the chemistry and charge storage ability, including capacitive properties and cycling stability in aqueous protic electrolyte, were determined. There is an inverse relationship between the prominence of the redox peaks and cycling stability; the latter increases with the niobium content. For instance, the capacitance retention after 20, 000 cycles is less than 1% for Ti2 CT x, but 78% for Ti0.4 Nb1.6 CT x . This study shows that electrochemical properties of MXenes can be controlled by tuning the ratio of transition metals in the MXene structure. Graphical Abstract: ga1 Highlights: Double-metal solid-solution MXenes (Ti2−y Nby T x and V2−y Nby T x ; 0 < y < 2) were synthesized and investigated. The capacitive properties and cycling stability of solid-solution MXenes directly depend on their composition. The redox peak intensity decreases while the cycling stability increases with the Nb content. This study provides a guide for adjusting the electrochemical properties of MXenes by tuning the M-site chemistry.